Role of sclerotherapy in vascular malformations - Mattassi, R. (Phlebologie, 2017)
Congenital vascular malformations (CVM) are a heterogeneous group of vessels defects that include venous, lymphatic, arteriovenous and combined anomalies. CVM may be located in every part of the body with great variability. A precise diagnostic process is required to get complete information about the anomaly prior to decide treatment between different options: surgery, sclerotherapy, embolization and laser. Sclerotherapy has a role in each type of CVM. However, correct indication, selection of the best sclerosing agent, and knowledge of technical skills in CVM are required for a good result. In venous malformations, ethanol is the most effective sclerosing agent but experience in management is required. Lymphatic malformations, mainly in the macrocystic form, can be treated easily with different substances. The nidus of arteriovenous malformations can be occluded by alcohol sclerosis. However, because of the high hemodynamic of AVM, treatment may be difficult; a good sclerosing technique is necessary to avoid complications and to get good results, which are always possible.
Keywords: Sclerotherapy; malformations; CVM; arteriovenous malformations; lymphatic malformations